2015
DOI: 10.1021/ie504393t
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Nonleaching Antimicrobial Linear Low-Density Polyethylene Films

Abstract: Antimicrobial packaging films have been widely used in various applications. However, because of concerns regarding safe food and consumer demands for preservative-free products, the antimicrobial agents applied to packaging have to be highly effective and the leaching effect is not allowed. In the present work, the antimicrobial agent polyhexamethylene guanidine hydrochloride was compounded with starch to prepare antimicrobial thermoplastic starch (ATPS). ATPS was then melt-blended with linear low-density pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…To evaluate antibacterial activities of the three types of graphene derivatives, the method reported by Liu et al 21,47 was used. E. coli cells (10 5 to 10 6 CFU mL À1 ) were incubated with fresh GO, FG or PHGH-G dispersions with different concentrations in PBS solutions at 37 C under 200 rpm shaking speed for 2 h. The death rate of bacterial cells was determined by the colony counting method described in the Experimental section, and the corresponding results are shown in Fig.…”
Section: Antibacterial Activities Of Go Fg and Phgh-gmentioning
confidence: 99%
“…To evaluate antibacterial activities of the three types of graphene derivatives, the method reported by Liu et al 21,47 was used. E. coli cells (10 5 to 10 6 CFU mL À1 ) were incubated with fresh GO, FG or PHGH-G dispersions with different concentrations in PBS solutions at 37 C under 200 rpm shaking speed for 2 h. The death rate of bacterial cells was determined by the colony counting method described in the Experimental section, and the corresponding results are shown in Fig.…”
Section: Antibacterial Activities Of Go Fg and Phgh-gmentioning
confidence: 99%
“…Furthermore, the antimicrobial property and biodegradation behavior of poly(butylene adipate-co-terephthalate) (PBAT)/TPS films before and after a three-month soil burial test have been studied. The results demonstrated that starch and PBAT were biodegradable, and TPS showed excellent growth inhibition against E. coli [ 422 ].…”
Section: Application Of Biodegradable Polymers and Antibacterial Poly...mentioning
confidence: 99%
“…This is the first attempt ever reported on rendering biodegradable polyester antimicrobial using guanidine-based polymer, as well as the impact on biodegradable behavior. As a further extension of the work above, Wang et al [50] co-extruded PHGH and starch to form antimicrobial thermoplastic starch (APTS), then compounded APTS with linear low-density polyethylene in the presence of a compatibilizer, polyethylene-grafted maleic anhydride. The resulting beads were used to prepare antimicrobial film via a blown filming process.…”
Section: Rendering Biodegradable Polymers and Cellulose-based Foammentioning
confidence: 99%